NUMERICAL INVESTIGATION OF THE CO-AXIAL IMPINGING JETS WITH VARIOUS DIAMETER RATIOS - Celik, Nevin; Bettenhausen, Daniel W. (Begell House Inc, 2012)
A predictive theory is presented which is capable of providing quantitative results for the heat transfer in impinging co-axial jets for the turbulent flow regime. The numerical solution is performed by making use of the CFX software package which discretizes the solution domain into quadrilateral elements. The heat transfer is calculated with the Nusselt number. The geometric variable parameter is the diameter ratio d/D (ratio of inner diameters of the inner and outer pipes). Other dependent parameters are dimensionless jet-to-impingement plate distance (H/D), Reynolds number (Re), and dimensionless radial distance (r/D). Local, average, and stagnation-point Nusselt numbers were found as the results of heat transfer analysis. It was found that local, average, and stagnation-point heat transfer with d/D attained a maximum at d/D = 0.55. For d/D = 0.55 and 0.35, for a given Reynolds number (10,000, 20,000, and 50,000), a co-axial jet yields higher heat transfer coefficients than a single jet.
Keywords: co-axial jet; numerical analysis; impingement